2017
DOI: 10.1515/jim-2017-0077
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary Shear Stress and CT Characteristics of Vulnerable Coronary Plaques

Abstract: Vulnerable coronary plaques are associated with a significant risk for rupture, and the ability to detect their characteristic features is of extreme importance, as timely detection of rupture-prone plaques could lead to the appropriate initiation of adequate therapeutic measures and prevent the evolution to an acute coronary event. The most common features of vulnerability in coronary plaques are represented by the presence of low density atheroma, a thin fibrous cap, spotty calcifications, and positive remod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Several recent studies identified areas with low ESS in the close vicinity of unstable coronary plaques [32]. At the same time, other studies suggested that rather than the low ESS, the high ESS could represent the factor triggering plaque vulnerability.…”
Section: Ess and Plaque Vulnerabilitymentioning
confidence: 97%
“…Several recent studies identified areas with low ESS in the close vicinity of unstable coronary plaques [32]. At the same time, other studies suggested that rather than the low ESS, the high ESS could represent the factor triggering plaque vulnerability.…”
Section: Ess and Plaque Vulnerabilitymentioning
confidence: 97%